[PDF] from uazone.org Enabling automated network services provisioning for cloud based applications using zero touch provisioning - Demchenko, Yuri; Filiposka, Sonja; Tuminauskas, Raimundas; Mishev, Anastas; Baumann, Kurt; Regvart, Damir; Breach, Tony (IEEE, 2015)
Modern research and education networks need to solve two major tasks: (1) providing seamless access to their users, and (2) support new scientific and collaborative applications that are becoming increasingly complex and dynamic in their scale, use of distributed resources, and required advanced networking services. Rapid deployment and automation of new network services provisioning is becoming difficult in large networks that incorporate different technologies and solutions. The task of providing seamless user experience in typically mobile and dynamically changing collaborative groups generates additional burdens for the configuration phases included in network provisioning. By introducing automation and enabling multipoint auto configuration of network devices, the Zero Touch Provisioning (ZTP) concept emerges as a possible alleviation of the complex network provisioning and infrastructure services deployment process. This paper investigates the characteristics of the ZTP model and discovers how ZTP can be used in order to enhance the services provided by the GEANT network and its associated National Research and Education Networks (NRENs) to the European research and education community. The future solution can be achieved by combining and enriching the existing provisioning models, solutions and practices available from different domains such as wireless networks, (complex) network management and operations services, and cloud based infrastructure services provisioning.
Keywords: Automated Network Provisioning, Automated Service Delivery, Cloud Infrastructure Services Provisioning, Network as a Service, Zero Touch Provisioning (ZTP).